Nitroisatin dithiocarbazate: Synthesis, structural characterization, DFT, and docking studies - Pereira, Pedro Henrique do Nascimento; Lima, Jackelinne Camargo; Deflon, Victor Marcelo; Malpass, Geoffroy Roger Pointer; de Oliveira, Ronaldo Junio; Maia, Pedro Ivo da Silva (European Journal of Chemistry, 2021)
The reaction between 5-nitroisatin with S-benzyl dithiocarbazate affords a new isatindithio carbazate so-called NO2Isadtc (Benzyl 2-(5-nitro-2-oxoindolin-3-ylidene)hydrazinecarbodi thioate) which was characterized by means of 1H NMR, FT-IR, UV-visible and single crystal X-ray diffraction - Crystal data for C16H12N4O3S2 (M =372.42 g/mol): triclinic space group P-1, (n°. 02), a = 6.640 Å, b = 8.256 Å, c = 15.908 Å, V = 849.6 Å3, Z = 2, T = 293 K, μ(MoKα) = 0.337 mm-1, Dcalc = 1.456 g/cm3, 27515 reflections measured (2.499° ≤ 2Θ ≤ 26.524°), 3518 unique (Rint = 0.0533, Rsigma =0.0222) which were used in all calculations. The final R1 was 0.0367 (I > 2σ(I)) and wR2 was 0.1045 (all data). Computational methods were applied to NO2Isadtc and its nonsubstituted parent compound Isadtc for structure optimization, electronic distribution, and infrared calculations using B3LYP functional with 6-31G(d,p) basis set in ethanol as a polarizable continuum model. Furthermore, docking studies using human thioredoxin reductase 1 (TrxR) as enzyme target also were performed using NO2Isadtc and the optimized structure of Isadtc. The results demonstrated that both NO2Isadtc and Isadtc may act as inhibitors of TrxR, having different interactions detected, highlighting the contact between the NO2 group and the S111 at the helix which is found for NO2Isadtc.